PRAKTEK EKSEKUSI OBJEK JAMINAN FIDUSIA YANG HILANG DALAM PERKARA ANTARA M. NASIR DENGAN PT. OLYMPINDO MULTI FINANCE (CONTOH KASUS: PUTUSAN NOMOR 950/Pid.B/2019/PN Jkt.Pst) - Malik Putra Eman; Stanislaus Atalim (Jurnal Hukum Adigama, 2021)
The execution of fiduciary collateral objects often experiences problems in the process. The loss of the collateral object is one of the obstacles in its execution. As in the example of the case where M. Nasri as the debtor has transferred the object of the fiduciary guarantee without the knowledge of PT. Olympindo Multi Finance as the creditor which causes the fiduciary collateral to disappear and causes difficulties in executing the collateral object. Constraints in the implementation of the fiduciary security object are in fact detrimental to creditors and cause difficulties in settling receivables due to default. In fact, the execution of the object of fiduciary collateral encounters various obstacles in practice, which of course can be found in the execution of the execution of the fiduciary guarantee object.